Some new species of Pseudocercospora associated with leaf spot in forest flora of North-eastern Uttar Pradesh - and S. NARAYAN, H.S.G. RAO, A.S. MOSES (Indian Phytopathology, 2002)
Three new species of Pseudocercospora from the Terai belt of North-eastern Uttar Pradesh, India, are described, illustrated and compared with allied species. The new species are P. lamiacearum on Salvia leucantha, P. lauracearum on Phoebe lanceolata and P. psoraleae on Psoralea cerelifolia.